2022
DOI: 10.3390/coatings12040489
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Use of Aloe vera Gel Alone and in Combination with Lemongrass Essential Oil as a Coating Material for Strawberry Fruits: HPLC and EDX Analyses

Abstract: Strawberry is a non-climacteric fruit but exhibits a limited postharvest life due to rapid softening and decay. A strawberry coating that is natural and safe for human consumption can be used to improve the appearance and safeguard the fruits. In this study, 20% and 40% Aloe vera gel alone or in combination with 1% lemongrass essential oil (EO) was used as an edible coating for strawberries. After application of all the treatments, the strawberry fruits were stored at a temperature of 5 ± 1 °C at a relative hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 90 publications
(108 reference statements)
1
1
0
Order By: Relevance
“…All the detected compounds possess multiple biological functions in the medicinal fields as well as cosmetics and food industry. Our data match with some results by Hassan et al [ 37 ] who observed that caffeic, coumaric, syringic, sinapic acid, cinnamic, and ferulic acid are the main acids of A. vera gel. Numan [ 38 ] confirmed the existence of phenolic compounds such as catechin, quercetin, aloe emodin, aloin, and sinapic acid in A. vera gel.…”
Section: Resultssupporting
confidence: 93%
“…All the detected compounds possess multiple biological functions in the medicinal fields as well as cosmetics and food industry. Our data match with some results by Hassan et al [ 37 ] who observed that caffeic, coumaric, syringic, sinapic acid, cinnamic, and ferulic acid are the main acids of A. vera gel. Numan [ 38 ] confirmed the existence of phenolic compounds such as catechin, quercetin, aloe emodin, aloin, and sinapic acid in A. vera gel.…”
Section: Resultssupporting
confidence: 93%
“…Phenolic acids and flavonoids in C. natator assayed in the current study were identified following the procedures described in Hassan et al (2022), Mosa et al (2021), andGalal-Khallaf et al (2022a), using an Agilent 1100 HPLC System (Agilent, CA, USA) equipped with a quaternary pump, UV/Vis detector and C18 column (125 mm × 4.60 mm, 5 mm particle size). All standards (HPLC grade) for commonly found phenolic acids and flavonoids were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Hplc Analysis For Total Phenolic Acids and Flavonoidsmentioning
confidence: 99%
“…Aloe vera is a succulent plant known for its gel-like substance containing bioactive compounds such as polysaccharides, phenolic, and flavonoids (Birtane & Beyler Çiğil, 2022). It was recorded as colorless, odorless, and not affecting the taste of the food, moreover, it was assesed as safe for the human health and ecofriendly (Hassan et al, 2022). Lemongrass, on the other hand, is a widely used herb known for its aromatic and medicinal properties, which are attributed to its high content of essential oils, phenolic, and terpenes (Azizah et al, 2023).…”
Section: Introductionmentioning
confidence: 99%